Land degradation and restoration in Lao Cai and Son La Provinces, northern mountainous region of Vietnam. Scoping study for the One CGIAR Initiative on Nature-Positive Solutions - Chien, Pham Duc; Nguyen, Van Truong; Hoang, Lien Son; Ha, Van Tiep; Hoang, Nguyen Viet Hoa; Jalonen, Riina (2023)
Vietnam is among the few countries worldwide that have experienced a net increase in forest cover in the past decades. Widespread tree planting efforts have provided important income sources for local communities, including ethnic minority groups. However, the emphasis has been on monocrop plantations of exotic tree species, which has yielded limited ecosystem service benefits such as biodiversity conservation and watershed protection. Simultaneously, ongoing land use changes and unsustainable farming practices contribute to worsening soil erosion and biodiversity loss, and increase the vulnerability of production systems and livelihoods to climate change. The OneCGIAR Initiative on Nature-positive solutions (NATURE+) seeks to co-create and implement agri-food systems that are based on nature-positive production practices and support local food and nutrition security and livelihoods, while simultaneously ensuring that agriculture is a net positive contributor to nature. This includes identifying effective and scalable approaches to restore degraded communal and smallholder lands and related ecosystem services, and identify opportunities to increase tree cover, including native tree species, in restoration efforts. The NATURE+ initiative is implemented in Vietnam’s Son La and Lao Cai provinces in the country’s Northern Mountainous region, as well as in India, Burkina Faso, Kenya and Colombia. The objective of this scoping study is to identify good practices, lessons learned and recommendations from past forest and landscape restoration efforts in Vietnam that have helped halt land degradation and biodiversity loss while simultaneously improving rural livelihoods. The findings of the study will be used to refine contextually relevant research and development interventions for NATURE+ in Vietnam.